Impact of leader creativity expectations, creative self-efficacy and leader-member exchange on creative performance: A mediating role of intrinsic motivation - Adil, Muhammad Shahnawaz (2021)
Creative performance of academicians is one of the major problems of higher education in the 21st century. The objective of this study is two-fold: a) to analyze the effects of leader creativity expectations, creative self-efficacy, and leader-member exchange on creative performance; and b) to investigate whether intrinsic motivation mediates the relationship between the three variables (i.e. leader creativity expectations, creative self-efficacy and leader-member exchange), and creative performance. Using simple random sampling technique, 281 valid responses are drawn on a survey questionnaire from the full-time academicians of 24 private universities of Karachi, Pakistan. Hypotheses are tested using partial least square structural equation modeling technique. The results show that: a) leader creativity expectations do not have significant effect on creative performance; b) both creative self-efficacy and leader-member exchange have significant effects on creative performance; c) on contrary to expectations, leader creativity expectations and leader-member exchange have significant but negative effects on intrinsic motivation; d) creative self-efficacy has significant positive effect on intrinsic motivation with moderate effect size; e) intrinsic motivation shows a significant effect on creative performance with the highest effect size; and f) intrinsic motivation significantly mediates the relationship between three variables (i.e. leader creativity expectations, creative self-efficacy and leader-member exchange), and creative performance. The findings suggest that the management of private universities should be careful in raising their creativity expectations and quality of leader-member exchange relationship because these contextual factors may reduce the intrinsic motivation of academicians for their creative performance